Kan poesien redde? Lyrikkens rolle hos Czesław Miłosz og i hans norske gjendiktning ved Paal Brekke - Wilkus-Wyrwa, Aleksandra (Folia Scandinavica Posnaniensia, 2016)
The purpose of the paper is to compare the original verse by Czesław Miłosz and its translated version by Paal Brekke. To discuss the images of the poetry and the poet in Campo di Fiori and Tilegnelse the comparative translation theory is applied and the poets' literary background brought into focus. In the next step such issues as the translator's figure and his influence on the target text are addressed. The paper presents that Brekke's literary work alters Miłosz's original poetics.